Negative electrode for lithium secondary battery and lithium secondary battery including the same

The lithium secondary battery design with a structured negative electrode active layer suppresses lithium dendrite formation by aligning carbon-based active material perpendicular to the collector, ensuring safety and high-rate performance.

JP2025502103AActive Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024541068
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-05-15
Filing Date
2023-09-15
Publication Date
2025-01-24
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

The formation of dendrites on the negative electrode surface during lithium secondary battery charging and discharging leads to internal short circuits, reducing safety and capacity, especially under high-rate conditions, due to variations in the N/P ratio and sliding phenomena at the electrode edges.

Method used

A lithium secondary battery design with a negative electrode active layer divided into flat and sloped portions, where the sloped portions have a carbon-based active material aligned nearly perpendicular to the current collector, maintaining a consistent thickness and suppressing lithium precipitation through controlled crystal plane orientation.

Benefits of technology

The design enhances safety and allows for prolonged high-rate charging and discharging by preventing lithium dendrite formation, maintaining a stable N/P ratio and reducing electrical resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502103000001_ABST
    Figure 2025502103000001_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a lithium secondary battery in which lithium deposition is suppressed and a lithium secondary battery including the same, the negative electrode having a form in which a carbon-based active material contained in a sliding portion of a negative electrode active layer has a high degree of alignment, and thus the negative electrode has an excellent effect of suppressing lithium deposition at an end of the negative electrode active layer during charging and discharging of the secondary battery, and thus a lithium secondary battery including the same has an advantage in that it is highly safe and can be charged and discharged for a long time under high rate conditions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0116873 filed on September 16, 2022 and Korean Patent Application No. 10-2023-0062304 filed on May 15, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a negative electrode for a lithium secondary battery in which lithium deposition during charging and discharging is suppressed, and a lithium secondary battery including the same. [Background technology]

[0003] 2. Description of the Related Art In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.

[0004] Such secondary batteries are power generating elements capable of being charged and discharged and have a laminated structure of a positive electrode / separator / negative electrode. In general, the positive electrode contains a lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based negative electrode active material such as graphite. During charging, lithium ions released from the positive electrode are absorbed into the carbon-based negative electrode active material of the negative electrode, and during discharging, the lithium ions contained in the carbon-based negative electrode active material are absorbed into the lithium metal oxide of the positive electrode, thereby allowing repeated charging and discharging.

[0005] One of the factors that influence the performance of a secondary battery is the capacity ratio of the active materials contained in the positive and negative electrodes. The capacity ratio can be expressed as the N / P ratio. The N / P ratio is the value obtained by dividing the total capacity of the negative electrode calculated by considering the capacity per unit area of ​​the negative electrode by the total capacity of the positive electrode calculated by considering the capacity per unit area of ​​the positive electrode, and since it has a significant effect on the safety and capacity of the battery, it is generally adjusted to have a value of 1 or more.

[0006] However, when manufacturing the positive and negative electrodes, a sliding phenomenon occurs at the ends of the electrode mixture layer containing the active material, where the thickness of the electrode mixture layer becomes thinner toward the outside, making it difficult to maintain a constant N / P ratio between the positive and negative electrodes. In particular, if the N / P ratio is less than 1, lithium ions are not fully intercalated into the negative electrode active material during charging of the battery, but are precipitated on the surface of the negative electrode to form dendrites. The likelihood of dendrites occurring increases significantly when a lithium secondary battery is used for a long time under high-rate conditions, and the dendrites formed in this way can induce an internal short circuit in the battery, thereby acting as a factor that impairs the safety of the battery.

[0007] In order to solve this problem, attempts have been made to manufacture a negative electrode by increasing the thickness of the edge where the sliding phenomenon occurs during the formation of the negative electrode composite layer. In this case, the negative electrode active material becomes highly densified at the edge of the negative electrode composite layer during rolling of the negative electrode composite layer, which reduces the lithium ion mobility at the edge, resulting in a limit to the deterioration of battery performance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2015-0028457 [Patent Document 2] Korean Patent Publication No. 10-2016-0125720 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a negative electrode for a lithium secondary battery in which lithium precipitation at the end of the negative electrode mixture layer is suppressed even when the lithium secondary battery is used for a long period of time under high-rate conditions, and a lithium secondary battery including the same. [Means for solving the problem]

[0010] To solve the above-mentioned problems, In one embodiment, the present invention comprises: a negative electrode current collector; and a negative electrode active layer provided on at least one surface of the negative electrode current collector and including a carbon-based negative electrode active material; The negative electrode active layer is divided into a flat portion having a constant thickness based on a cross-sectional structure in a thickness direction, and a sliding portion disposed at an end of the flat portion and having a thickness gradient, The sliding portion provides a negative electrode for a lithium secondary battery, in which the value according to the following formula 1 is 1.0 or less when analyzed by near-edge X-ray absorption fine structure (NEXAFS) spectroscopy.

[0011]

number

[0012]

number

[0013]

number

[0014] In formulas 1 to 3, S 60 / 0 is the peak intensity ratio when the X-ray incident angle is 0° (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ), I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 Arepresents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

[0015] At this time, the sliding portion has an alignment degree (OI sliding ) is the degree of alignment (OI) of the carbon-based negative electrode active material contained in the flat part. flat ) may be lower.

[0016] [Formula 4] OI=I 004 / I 110

[0017] In Equation 4, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer.

[0018] Specifically, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the flat portion flat ) is the degree of alignment (OI) of the carbon-based negative electrode active material contained in the sliding part. sliding ) can be 110% to 200%.

[0019] In addition, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the sliding portion sliding ) can be 0.1 to 0.6.

[0020] In addition, the sliding portion is characterized by a ratio (I 004 / I 002 ) may be 0.04 or greater.

[0021] Meanwhile, the negative electrode current collector may be divided into a coated portion where a negative electrode active layer is disposed and a plain portion where a negative electrode active layer is not disposed, and the sliding portion may be adjacent to a plain portion where a negative electrode tab is provided among the plain portions.

[0022] At this time, the sliding part may have a width of 1 mm to 30 mm based on a cross-sectional structure in the thickness direction of the negative electrode active layer.

[0023] The carbon-based negative electrode active material may include at least one of natural graphite and artificial graphite, and may have a spherical particle shape with a high sphericity of 0.75 or more.

[0024] Further, in one embodiment, the present invention provides There is provided a lithium secondary battery comprising an electrode assembly including a positive electrode, the above-described negative electrode according to the present invention, and a separator disposed between the positive electrode and the negative electrode.

[0025] In this case, the positive electrode may include a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector and containing one or more positive electrode active materials selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2.

[0026] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2

[0027] [Chemical formula 2] LiM 2 p Mn 1-p O4

[0028] In the above Chemical Formula 1 and Chemical Formula 2, M 1is one or more of the elements W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつy+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is in the range of 0.05≦p≦1.0.

[0029] Specifically, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O4, LiNi 0.3 Mn 1.7 O4, LiFePO4, LiFe 0.8 Mn 0.2 PO4, and LiFe 0.5 Mn 0.5 It may contain one or more of the following:

[0030] Also, the electrode assembly may be a stacked electrode assembly, a zigzag electrode assembly, or a zigzag-stack electrode assembly. Effect of the Invention

[0031] The negative electrode for a lithium secondary battery according to the present invention has an alignment degree (S 60 / 0 and / or OI) is low, which has an excellent effect of suppressing lithium deposition on the surface of the negative electrode active layer, specifically at the end, during charging and discharging of the secondary battery. Therefore, a lithium secondary battery including the same has the advantage of being highly safe and capable of being charged and discharged for a long time under high rate conditions. [Brief description of the drawings]

[0032] [Figure 1] FIG. 2 is a cross-sectional view showing a cross-sectional structure of a negative electrode produced in one embodiment according to the present invention. [Diagram 2] FIG. 4 is a cross-sectional view showing a cross-sectional structure of a negative electrode produced in another embodiment according to the present invention. [Diagram 3] 13 is an image showing the alignment of the ab-axis crystal planes of graphite depending on whether or not a magnetic field is applied to a negative electrode slurry during the formation of a negative electrode active layer, where (a) shows the case where no magnetic field is applied and the graphite crystal planes are not aligned, and (b) shows the case where a magnetic field is applied and the graphite crystal planes are aligned. [Figure 4] This is an image showing the tendency of the type and position of each orbital absorption peak depending on the angle of incidence of X-rays during near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. (a) shows the type and position of the orbital that forms the double bond of graphite, and (b) shows the peak shape of each orbital position when X-rays are incident. [Diagram 5] 1 is an image showing an incident angle of X-rays during Near Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy analysis of a negative electrode manufactured according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be described in detail.

[0034] However, this is not intended to limit the invention to any particular embodiment, but it should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.

[0035] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and may be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0036] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.

[0037] In addition, in the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of a defined component based on the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite based on the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.

[0038] In addition, in the present invention, the "cross-sectional structure" refers to a structure of a surface cut in the thickness direction of the negative electrode active layer, or a structure of a surface cut perpendicularly based on the surface of the negative electrode active layer. In this case, the cut surface may be the same as a surface cut perpendicularly to the process direction when forming the negative electrode active layer, or a surface cut in the width direction of the negative electrode slurry applied to form the negative electrode active layer. In addition, the cross-sectional structure may be a structure of a surface cut in the thickness direction of the negative electrode active layer, and may have a structure cut in a direction proceeding from one surface on which the negative electrode tab is formed to the opposite surface. That is, it may have a thickness-wise cut structure in which the negative electrode tab is provided on one side.

[0039] In addition, in this specification, "the carbon-based negative electrode active material is oriented" or "the carbon-based negative electrode active material is aligned" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material constituting the negative electrode active material particles is arranged to have a predetermined inclination based on the surface of the negative electrode current collector, as shown in (b) of Figure 3. This may be different from (a) of Figure 3, in which the particles of the carbon-based negative electrode active material themselves are aligned in a predetermined direction only inside the negative electrode active layer, but have no directionality with respect to the negative electrode current collector.

[0040] In addition, "high orientation of the carbon-based negative electrode active material" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer has a high frequency of having a certain inclination with respect to the surface of the negative electrode current collector. In some cases, it may mean that the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, more than 45°, specifically 60° or more) with respect to the surface of the negative electrode current collector.

[0041] In addition, "high degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" referred to in this specification is large, and a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a low angle (e.g., less than 45°) with respect to the surface of the negative electrode current collector. Conversely, "low degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" is small, and the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, 45° or more, specifically 60° or more) with respect to the surface of the negative electrode current collector.

[0042] Furthermore, in this specification, the term "average particle size (D 50 ) refers to the particle size at which the cumulative value in the particle size distribution of the particles is 50%, and is also called the median diameter.

[0043] The present invention will now be described in more detail.

[0044] <Negative electrodes for lithium secondary batteries> In one embodiment, the present invention comprises: a negative electrode current collector; and a negative electrode active layer provided on at least one surface of the negative electrode current collector and including a carbon-based negative electrode active material; The negative electrode active layer is divided into a flat portion having a constant thickness based on a cross-sectional structure in a thickness direction, and a sliding portion disposed at an end of the flat portion and having a thickness gradient, The sliding portion provides a negative electrode for a lithium secondary battery, in which the value according to the following formula 1 is 1.0 or less when analyzed by near-edge X-ray absorption fine structure (NEXAFS) spectroscopy.

[0045]

number

[0046] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode active layer containing a carbon-based negative electrode active material on at least one surface of a negative electrode current collector.

[0047] Here, the negative electrode active layer refers to a layer that realizes the electrical activity of the negative electrode. The negative electrode active layer includes a carbon-based negative electrode active material as a negative electrode active material in order to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the battery. Specifically, the carbon-based negative electrode active material means a material mainly composed of carbon atoms, and such a carbon-based negative electrode active material may include graphite. The graphite may include at least one of natural graphite and artificial graphite. For example, the carbon-based negative electrode active material may include natural graphite or artificial graphite alone, or may include a mixture of natural graphite and artificial graphite in some cases. In this case, the mixture ratio of natural graphite and artificial graphite may be 5 to 40:60 to 95, or 10 to 30:70 to 90, based on weight. The carbon-based negative electrode active material contains natural graphite and artificial graphite in the above-mentioned mixing ratio, and thus can realize high orientation of the carbon-based negative electrode active material on the surface of the negative electrode current collector while strengthening adhesion between the negative electrode current collector and the negative electrode active layer.

[0048] The carbon-based negative electrode active material is preferably a spherical graphite granule formed by the aggregation of a plurality of flake graphite. Examples of flake graphite include natural graphite, artificial graphite, mesophase calcined carbon (bulk mesophase) made from tar and pitch, graphitized cokes (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. In particular, a graphite granule assembled from a plurality of natural graphites having high crystallinity is preferable. Also, one graphite granule may be formed by the aggregation of 2 to 100 flake graphite particles, preferably 3 to 20 flake graphite particles.

[0049] Such a carbon-based negative electrode active material, specifically, graphite, may have a spherical particle shape, and the sphericity of the graphite particles may be 0.75 or more, for example, 0.75 to 1.0, 0.75 to 0.95, 0.8 to 0.95, or 0.90 to 0.99. Here, the "sphericity" may refer to the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle, and when the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer, or may be determined by measuring the particle shape using a scanning electron microscope (SEM) or an energy dispersive spectrometer, and then analyzing the measurement results.

[0050] The present invention has the advantages that, by realizing a nearly spherical shape of the carbon-based negative electrode active material, the electrical conductivity of the negative electrode active layer can be increased, thereby improving the capacity of the battery, and that, by increasing the specific surface area per unit weight of the negative electrode active material, the adhesive strength between the negative electrode active layer and the current collector can be improved.

[0051] In addition, the carbon-based negative electrode active material has an average particle size (D 50 ), specifically, the average particle size (D 50 ) can be shown.

[0052] The average particle size of the carbon-based negative electrode active material is preferably as small as possible to prevent the particles from expanding due to charging with lithium ions, and to maximize the degree of disorder in the direction of expansion of each particle. However, if the particle size of the carbon-based negative electrode active material is less than 0.5 μm, the number of particles per unit volume increases, and a large amount of binder is required, which may reduce the sphericity and sphericity yield. On the other hand, if the maximum particle size exceeds 10 μm, the expansion rate of the negative electrode active material during charging and discharging of the secondary battery increases significantly, and the adhesion between the particles of the negative electrode active material and the adhesion between the negative electrode active material particles and the current collector decreases due to repeated charging and discharging, and the cycle characteristics may be significantly reduced.

[0053] In addition, the negative electrode active layer may be prepared by applying a negative electrode slurry including a carbon-based negative electrode active material to at least one surface of a negative electrode current collector, followed by drying and rolling the same, in order to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the secondary battery.

[0054] Referring to FIG. 1 and FIG. 2, the cross-sectional structure of the negative electrode will be described. The negative electrode active layers 120 and 220 of the present invention are divided into flat portions 121 and 221 having a uniform thickness at the center based on the cross-sectional structure, and sliding portions 122a, 122b and 222 having a thickness gradient at the edges of the flat portions, i.e., at the ends of the flat portions.

[0055] The flat portions 121 and 221 are regions constituting most of the negative electrode active layers 120 and 220, and may have a ratio of 80% or more, 85% or more, 90% or more, 93% or more, 95% or more, 97% or more, 96% to 99%, 98% to 99.5%, or 98.5% to 99.9% of the total length in the width direction based on the cross-sectional structure of the negative electrode active layers 120 and 220. As a result, the sliding portions 122a, 122b, and 222 located at the ends of the flat portions 121 and 221 and constituting the negative electrode active layers 120 and 220 together with the flat portions may have a ratio of 20% or less, 15% or less, 10% or less, 7% or less, 5% or less, 3% or less, 1% to 4%, 0.5% to 2%, or 0.1 to 1.5% of the total length in the width direction based on the cross-sectional structure of the negative electrode active layers. In this case, the sliding portions 122a, 122b, and 222 may have a width of 1 mm to 30 mm from the boundary line with the negative electrode current collectors 110 and 210 to the inside of the negative electrode active layer based on the cross-sectional structure of the negative electrode active layer, and specifically may have a width of 1 mm to 5 mm, 1 mm to 10 mm, 1 mm to 20 mm, 5 mm to 10 mm, 5 mm to 15 mm, 5 mm to 25 mm, 10 mm to 20 mm, 10 mm to 30 mm, 15 mm to 30 mm, or 20 mm to 30 mm.

[0056] Here, the "width direction of the negative electrode active layer" may refer to a direction perpendicular to the running direction C of the negative electrode current collector on the surface of the negative electrode active layer (or negative electrode slurry) during the manufacture of the negative electrode. It may also be the same as the direction proceeding from one side of the negative electrode active layer on which the negative electrode tab (not shown) of the manufactured negative electrodes 100 and 200 is formed to the other side opposite thereto. By adjusting the length ratio and / or width length of the flat portions 121 and 221 and the sliding portions 122a, 122b and 222 within the above ranges, the present invention may further increase the energy density of the negative electrode and at the same time prevent a decrease in productivity during the manufacture of the negative electrode.

[0057] Meanwhile, the negative electrode current collectors 110 and 210 provided in the negative electrodes 100 and 200 are divided into a coated portion where the negative electrode active layers 120 and 220 are disposed, and a plain portion where the negative electrode active layers 120 and 220 are not disposed, and a negative electrode tab for electrically connecting to a negative electrode terminal may be provided on any one of the plain portions.

[0058] Here, the sliding portion of the negative electrode active layer may be located on the entire edge of the flat portion or may be selectively located on a portion. Preferably, the sliding portions 122a and 222 are located on the edges of the negative electrode active layers 120 and 220 and form a boundary line by contacting the uncoated portions of the negative electrode current collectors 110 and 210, and the uncoated portions may be the uncoated portions 111a and 211a on which the negative electrode tabs are provided. In the region where the negative electrode tabs are located, a high current density is induced due to the bias of the electrochemical reaction, and the electrical resistance acts large, so that lithium deposition easily occurs on the surface of the negative electrode active layer adjacent to the negative electrode tabs. However, when the sliding portions 122a and 222a of the present invention are disposed at positions that form a boundary line (e.g., a first boundary line) with the negative electrode uncoated portions 111a and 211a on which the negative electrode tabs are provided, the ab-axis crystal plane orientation of the carbon-based negative electrode active material contained in the sliding portions is controlled, and the electrical resistance of the negative electrode active layer adjacent to the negative electrode tabs can be reduced, thereby preventing lithium from being precipitated in a dendritic form.

[0059] As an example, when the negative electrode 100 is manufactured through a roll-to-roll process, the sliding portions 122a and 122b may be located at the edge of the negative electrode active layer 120 as shown in Fig. 1, and may be disposed at a first edge of the negative electrode active layer 120 that is in contact with a first uncoated portion 111a having a negative electrode tab provided thereon to form a first boundary line, and a second edge of the negative electrode active layer 120 that is in contact with a second uncoated portion 111b facing the first uncoated portion 111a to form a second boundary line facing the first boundary line. In this case, the third and fourth edges of the negative electrode active layer adjacent to the first and second edges may have cut surfaces due to slitting during the manufacture of the negative electrode, and therefore, there may be no sliding portion having a thickness gradient of the negative electrode active layer.

[0060] As another example, the sliding portion 222 may be disposed only at an edge of the negative electrode active layer 220 that is in contact with the first uncoated portion 211a where the negative electrode tab is provided and forms a first boundary line, as shown in Fig. 2. In this case, a cut surface (corresponding to S / F in Fig. 1) due to slitting during the manufacture of the negative electrode may be present at a second edge of the negative electrode active layer 120 that is opposite to the first boundary line and forms a second boundary line, and therefore, a sliding portion having a thickness gradient of the negative electrode active layer may not be present.

[0061] In addition, the sliding portions 122a, 122b, and 222 have a thickness gradient in which the thickness decreases as the distance increases from the point where the sliding portions 122a, 122b, and 222 contact the flat portions 121 and 221, since a sliding phenomenon of the negative electrode slurry containing the negative electrode active material is induced at the end of the negative electrode active layer during the manufacture of the negative electrode. Specifically, the negative electrode slurry used during the manufacture of the negative electrode active layer has a form in which graphite, which is a carbon-based negative electrode active material, is mixed with a dispersion medium. In this case, water is usually used as the dispersion medium. Water is a solvent with a high surface tension, and the negative electrode slurry containing water exhibits a phenomenon in which the surface area exposed to the air after being applied to the negative electrode current collector is reduced due to the high surface tension of water. As a result, the negative electrode slurry applied to the negative electrode current collector induces a sliding phenomenon that attempts to form a curved surface having a predetermined angle with the surface of the negative electrode current collector inside the negative electrode slurry.

[0062] However, this sliding phenomenon generally occurs when it is difficult to maintain a constant N / P ratio between the positive and negative electrodes. In particular, when the N / P ratio is less than 1, lithium ions are not fully intercalated into the carbon-based negative electrode active material during battery charging, and are instead deposited on the surface of the negative electrode to form dendrites. The likelihood of dendrites occurring increases significantly, particularly when a lithium secondary battery is used for a long period of time under high-rate conditions. The dendrites thus formed may induce an internal short circuit in the battery, and thus may act as a factor that impairs the safety of the battery.

[0063] However, the present invention can prevent lithium from being deposited in a dendritic form on the surface of the negative electrode during charging and discharging by controlling the crystal plane orientation of the carbon-based negative electrode active material contained in the sliding portion as shown in Figure 3. Specifically, the sliding portion can include a carbon-based negative electrode active material in which the ab-axis crystal plane, which indicates the two-dimensional planar structure of the carbon-based negative electrode active material, is aligned nearly perpendicular to the negative electrode current collector.

[0064] Here, "the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector" may mean that the crystal plane of the carbon-based negative electrode active material constituting the spherical particles, specifically, the ab-axis crystal plane indicating the planar direction of graphite having a two-dimensional structure among the crystal planes of graphite, is aligned at an inclination nearly perpendicular to the surface of the negative electrode current collector. In this case, the planar direction of the graphite (i.e., the ab-axis crystal plane direction) may have an average inclination of 60° to 120°, preferably 70° to 110°, or 80° to 100°, relative to the negative electrode current collector.

[0065] In addition, the alignment of the carbon-based negative active material may be applied by any method commonly used in the art, but specifically, after applying a magnetic field to the surface of the negative electrode slurry containing the carbon-based negative active material on the surface of the negative electrode current collector, the alignment may be induced by orienting the negative electrode slurry at the upper and lower parts of the negative electrode slurry. At this time, the magnetic field may be applied only to the sliding part of the negative electrode slurry, but in the present invention, a method in which the magnetic field is applied to the entire surface of the negative electrode slurry including the flat part and the sliding part may be applied. The negative electrode slurry located at the sliding part during the manufacture of the negative electrode forms a predetermined angle with the negative electrode current collector due to the thickness gradient. The angle of the sliding part thus embodied increases the exposure of the magnetic field applied to the carbon-based negative active material when the magnetic field is applied to the entire surface of the negative electrode slurry, and therefore acts as a factor for applying a magnetic field greater than the strength of the magnetic field applied to the flat part. In this case, each of the carbon-based negative active materials contained in the sliding portion and the flat portion is aligned to have a predetermined inclination with respect to the negative current collector. Also, since the carbon-based negative active material in the sliding portion is aligned at a high angle close to perpendicular to the surface of the negative current collector, it may be embodied with a relatively lower degree of alignment compared to the carbon-based negative active material in the flat portion. In contrast, when a magnetic field is applied only to the negative electrode slurry located in the sliding portion during the manufacture of the negative electrode, the carbon-based negative active material contained in the sliding portion may be aligned close to perpendicular to the negative current collector, but there is a limit in that the alignment is not uniform.

[0066] The degree of alignment of the carbon-based negative electrode active material can be adjusted by the strength of the applied magnetic field, the exposure time, etc. For example, when a magnetic field is applied to the surface of the negative electrode slurry containing the carbon-based negative electrode active material for 1 to 10 seconds, the ab-axis crystal plane of the carbon-based negative electrode active material of the negative electrode slurry to which the magnetic field is applied for 10 seconds may have a larger inclination with respect to the surface of the negative electrode current collector than the carbon-based negative electrode active material of the negative electrode slurry to which the magnetic field is applied for 1 second. In the present invention, the magnetic field application to the negative electrode slurry may be performed at an intensity of 0.5T to 2.0T for 1 to 60 seconds, specifically, at an intensity of 0.8T to 1.5T or 0.8T to 1.2T for 1 to 30 seconds or 1 to 20 seconds. In addition, the magnet used when applying a magnetic field to the negative electrode slurry may have a length ratio of 105% to 200% based on the width direction of the negative electrode slurry, and specifically, may have a length ratio of 110% to 180%, 110% to 160%, 110% to 140%, 110% to 130%, 130% to 150%, or 105% to 120% based on the width direction length of the negative electrode slurry. By adjusting the length ratio of the magnet placed on the surface of the negative electrode slurry when applying a magnetic field to the negative electrode slurry as described above, the present invention can apply a magnetic field more uniformly to the entire exposed surface of the sliding part.

[0067] Meanwhile, the degree of alignment of the carbon-based negative active material contained in the negative active layer may be determined by molecular orientation and / or crystal structure analysis of the carbon-based negative active material.

[0068] As one example, in the sliding portion of the negative electrode active layer, the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector, and the value according to the following formula 1 may be 1.0 or less when analyzed by near-edge X-ray absorption fine structure (NEXAFS) spectroscopy.

[0069]

number

[0070] (In the above formula 1, S 60 / 0 is the peak intensity ratio (I0 B / A) when the X-ray incidence angle is 60° (I60 B / A ) represents the value of

[0071] Unlike X-ray photoelectron spectroscopy (XPS), which measures the bond energy between atoms constituting a compound, near-edge X-ray absorption fine structure (NEXAFS) spectroscopy can only reflect the local structure near the carbon atom including the excited core electron and the surface structure of the particles of the measured carbon-based negative electrode active material. Therefore, the present invention can measure the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer by using a spectrum obtained by NEXAFS spectroscopy on the negative electrode active layer.

[0072] Specifically, when X-rays are irradiated onto the carbon atom (C) of a carbon-based negative electrode active material, the occupied electrons (K-shell inner shell electrons) present in the inner shell level (1s orbital) of the carbon atom absorb the X-ray energy and are excited to various vacant molecular orbitals in an unoccupied state, and the NEXAFS spectroscopy analysis uses the absorption spectrum observed at this time. Here, the above-mentioned vacant molecular orbitals include, in the case of graphite, which is a carbon-based negative electrode active material, i) π* orbital assigned to the antibonding orbital of sp2 bonds that reflects the crystallinity (basal plane, orientation, etc.) of graphite, ii) σ* orbital assigned to the antibonding orbital of sp3 bonds that reflects the crystallinity disorder (edge ​​plane, non-orientation, etc.), and iii) Rydberg assigned to the antibonding orbital of CH bonds, CO bonds, etc.

[0073] Carbon-based negative electrode active materials, such as graphite, have a crystal structure in which carbon atoms are stacked in a hexagonal network structure (see FIG. 4(a)) formed by sp2 bonds, with the basal plane being the two-dimensional plane (ab-axis crystal plane) of the hexagonal network surface, and the plane showing the end of the hexagonal network (c-axis crystal plane) being the edge plane. In the edge plane of the carbon-based negative electrode active material, -COOH, -C=O, etc. may be present in the terminal carbon, so the sp3 bond ratio may be high. Therefore, in order to analyze the crystal plane orientation and / or alignment of the carbon-based negative electrode active material, it is necessary to analyze the state of the sp2 orbital of the carbon atom in each crystal plane of the carbon-based negative electrode active material.

[0074] The NEXAFS spectroscopy may be performed by a total electron yield method in which the negative electrode active layer is irradiated with X-rays having a fixed angle of incidence with respect to the negative electrode active layer, and the energy of the irradiated X-rays is scanned from 280 eV to 320 eV while measuring the current flowing through the negative electrode active layer to supplement the photoelectrons emitted from the surface of the negative electrode active layer.

[0075] At this time, since the synchrotron radiation is X-rays linearly polarized by applying a magnetic field E, the intensity of the absorption peak observed may vary depending on the direction of incidence of the X-rays. Specifically, referring to FIG. 4(a), in the case of graphite, which is a carbon-based negative electrode active material, a hexagonal network structure is formed through the sp2 bonds (-C=C-) of carbon atoms, and the sp2 bonds include σ orbitals located in a direction parallel to the sp2 bonds and π orbitals located in a direction perpendicular to the sp2 bonds. Here, the σ orbitals and π orbitals have a symmetrical structure with nodes at the nuclei of the carbon atoms and the σ* orbitals and π* orbitals, which are antibonding orbitals, respectively, so that the σ* orbitals and π* orbitals have the same directionality as the σ orbitals and π orbitals.

[0076] Therefore, as shown in Figure 4(b), when the incident direction of X-rays is parallel to the sp2 bond, the intensity of the absorption peak excited from the 1s level of carbon to the π* level becomes large, and conversely, when it is perpendicular to the sp2 bond, the intensity of the absorption peak becomes small. On the other hand, when the incident direction of X-rays is parallel to the sp2 bond, the intensity of the absorption peak excited from the 1s level to the σ* level becomes small, and conversely, when it is perpendicular to the sp2 bond, the intensity of the absorption peak becomes large.

[0077] Due to these characteristics, when the graphite contained in the negative electrode active layer has a high degree of orientation as shown in Figure 3(b), the vacant antibonding molecular orbitals of the graphite located on the surface of the negative electrode active layer are uniformly aligned, so when the angle of incidence of the X-rays on the negative electrode active layer is changed, the spectral shape changes significantly due to reinforcement and interference of the emitted photoelectrons. In contrast, when the graphite contained in the negative electrode active layer has a low degree of orientation as shown in Figure 3(a), the vacant antibonding molecular orbitals of the graphite located on the surface of the negative electrode active layer are non-uniformly aligned, so the spectral shape hardly changes even when the angle of incidence of the X-rays on the sample is changed.

[0078] In the present invention, in order to measure the degree of orientation of the carbon-based negative electrode active material contained in the negative electrode active layer, a NEXAFS spectroscopy analysis is performed on the surface of the negative electrode active layer, and X-rays are incident on the negative electrode active layer at different incident angles (0° and 60°). The ratio of the intensity of the absorption peak (peak B = 293 ± 0.2 eV) attributable to the transition from the 1s level to the σ* level of carbon to the intensity of the absorption peak (peak A = 287 ± 0.2 eV) attributable to the transition from the 1s level to the π* level of carbon for each incident angle (I B / A ), the ratio of the intensity ratio between the incidence angles (60° and 0°) (S 60 / 0 =I60 B / A / I0 B / A ) can be used to quantitatively measure the orientation and / or alignment of the carbon-based negative electrode active material contained in the negative electrode active layer.

[0079] That is, the degree of orientation of the carbon-based negative electrode active material contained in the sliding portion is expressed by i) the intensity of the absorption peak (peak A = 287 ± 0.2 eV) attributed to the transition from the 1s level to the π* level of carbon measured at an X-ray incidence angle of 60° (I60 A ) for the absorption peak (peak B = 293 ± 0.2 eV) intensity attributable to the transition from the 1s level of carbon to the σ* level (I60 B ) percentage (I60 B / A ) was calculated, and ii) the absorption peak (peak A = 287 ± 0.2 eV) intensity (I0 A ) for the absorption peak (peak B = 293 ± 0.2 eV) intensity attributable to the transition from the 1s level to the σ* level of carbon (I0 B ) percentage (I0 B / A ) and then iii) calculate their ratio (S 60 / 0 =I60 B / A / I0 B / A ) can be evaluated.

[0080]

number

[0081]

number

[0082] In Equation 2 and Equation 3, I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

[0083] Here, the above formula 1(S 60 / 0 ) indicates that the orientation of the ab-axis crystal plane of graphite, which is a carbon-based negative electrode active material, relative to the negative electrode current collector is low and the degree of alignment (OI) is high as the value is closer to 1, and that the orientation of the ab-axis crystal plane of graphite relative to the negative electrode current collector is high and the degree of alignment (OI) is low as the value is closer to 0. The sliding portion according to the present invention has a value (S 60 / 0 ) may be 1.0 or less, and more specifically may be 0.9 or less, 0.8 or less, 0.7 or less, 0.5 or less, 0.05 to 0.7, 0.05 to 0.5, 0.05 to 0.4, 0.1 to 0.7, 0.3 to 0.7, or 0.5 to 0.8.

[0084] The sliding portion of the negative electrode active layer according to the present invention is represented by the formula 1 (S 60 / 0 ) being 1 or less means that the ab-axis crystal plane of the carbon-based negative electrode active material contained in the sliding portion is aligned nearly perpendicular to the negative electrode current collector as shown in FIG. 3(b), and that the negative electrode including the same can suppress lithium deposition at the end of the negative electrode active layer during charging and discharging of the secondary battery.

[0085] This is also because the particles of the carbon-based negative electrode active material are 60 / 0 ) is 1 or less. 60 / 0 ) being 1 or less means that the ab-axis crystal planes of molecular crystals forming the particles of the carbon-based anode active material are aligned with a predetermined directionality within the particles. Therefore, when such a carbon-based anode active material is included in the anode active layer, the ab-axis crystal planes of the carbon-based anode active material tend to be non-oriented with respect to the surface of the anode current collector as shown in Figure 3(a) unless a separate treatment is performed, and this is differentiated from the sliding portion of the anode active layer according to the present invention.

[0086] In another example, the sliding portion of the negative electrode active layer is such that the ab-axis crystal plane of the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector, and the degree of alignment (OI) of the carbon-based negative electrode active material, which is represented by the following formula 4, is obtained by X-ray diffraction (XRD) spectroscopy analysis. sliding ) is the degree of alignment (OI) of the carbon-based negative electrode active material contained in the flat portion. flat ) can be smaller.

[0087] [Formula 4] OI=I 004 / I 110

[0088] In Equation 4, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer.

[0089] The crystal plane orientation of the carbon-based negative electrode active material can be determined by a crystal plane analysis of the carbon-based negative electrode active material, such as X-ray diffraction spectroscopy. The degree of alignment (OI) of the carbon-based negative electrode active material represented by the above formula 4 can be an index indicating the direction in which the crystal structure of the carbon-based negative electrode active material is aligned during X-ray diffraction measurement, specifically, the degree to which the ab-axis crystal plane indicating the two-dimensional planar structure of the carbon-based negative electrode active material is aligned with respect to the surface of the negative electrode current collector. For example, when the negative electrode active layer contains graphite as the carbon-based negative electrode active material, the negative electrode active layer exhibits 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°, which are peaks for graphite during X-ray diffraction measurement of the negative electrode active layer. This refers to the (0,0,2) plane, (1,0,0) plane, (1,0,1)R plane, (1,0,1)H plane, (0,0,4) plane, and (1,1,0) plane of the graphite crystal planes contained in the negative electrode active layer. In general, in the case of graphite, graphene layers are placed on the a-axis and b-axis planes, and such graphene layers are stacked along the c-axis to have a hexagonal or rhombohedral crystal structure. Here, the crystal plane peak is a peak that indicates the plane characteristics of such a crystal structure. In addition, the peak that appears at 2θ=43.4±0.2° may be considered to have appeared due to overlap of the (1,0,1)R plane of the carbon-based material and the peak corresponding to the (1,1,1) plane of the current collector, for example, Cu.

[0090] In the present invention, the degree of alignment (OI) of graphite can be measured by the area ratio of the peak at 2θ=54.7±0.2° indicating the (0,0,4) plane and the peak at 2θ=77.5±0.2° indicating the (1,1,0) plane, specifically, the area ratio obtained by integrating the intensities of the above peaks. In addition, the X-ray diffraction was measured using CuKα radiation as a target line, and the target line was extracted and measured using a monochromator device to improve the peak intensity resolution. At this time, the measurement conditions were 2θ=10°-90°, a scan speed (° / s) of 0.044-0.089, and a step size of 0.026° / step.

[0091] In addition, the (0,0,4) plane appearing at 2θ=54.7±0.2° indicates the thickness direction characteristic (c-axis direction characteristic) of the layered structure in which the two-dimensional planar structures of the graphite layers are stacked, and the (1,1,0) plane appearing at 2θ=77.5±0.2° indicates the planar characteristic (ab-axis direction characteristic) of the stacked graphite layers. Therefore, the smaller the (0,0,4) plane peak indicating the thickness direction characteristic of the graphite layer plane, and the larger the (1,1,0) plane peak indicating the planar characteristic of the graphite layer, the higher the angle of the graphite plane is aligned with respect to the negative electrode current collector surface. In other words, the closer the OI value is to 0, the closer the angle or inclination of the graphite layer plane with respect to the negative electrode current collector surface is to 90°, and the larger the OI value is, the closer the inclination with respect to the negative electrode current collector surface is to 0° or 180°.

[0092] In this respect, in the sliding portion of the negative electrode active layer according to the present invention, the ab-axis crystal plane of the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector, so that the degree of alignment (OI) of the carbon-based negative electrode active material contained in the sliding portion is reduced. sliding ) is the degree of alignment (OI) of the carbon-based negative electrode active material contained in the flat portion of the negative electrode active layer. flat Specifically, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the sliding portion may be relatively low. sliding ) may be 0.1 to 0.8, and more specifically may be 0.15 to 0.8, 0.15 to 0.6, 0.15 to 0.5, 0.2 to 0.5, 0.2 to 0.4, 0.25 to 0.45, 0.3 to 0.5, 0.3 to 0.8, 0.4 to 0.7, or 0.35 to 0.6.

[0093] The present invention is directed to improving the alignment degree (OI) of the carbon-based negative electrode active material contained in the sliding portion. sliding By controlling the N / P ratio within the above range, it is possible to improve the lithium ion mobility at the negative electrode end during charging and discharging of the battery while reducing the electrode resistance, and therefore it is possible to prevent the N / P ratio from being reversed even if the thickness of the negative electrode active layer end is thinner than that of the positive electrode active layer end.

[0094] In addition, the carbon-based negative electrode active material contained in the flat portion is oriented together with the carbon-based negative electrode active material contained in the sliding portion, and the ab-axis crystal plane may have a certain angle or inclination with respect to the surface of the negative electrode current collector. As a result, the carbon-based negative electrode active material contained in the flat portion has an alignment degree (OI flat Specifically, the carbon-based negative electrode active material contained in the flat portion has an alignment degree (OI) that satisfies a predetermined range. flat ) is the alignment degree (OI) of the carbon-based negative electrode active material contained in the sliding part. sliding The carbon-based negative electrode active material contained in the flat portion may have a ratio of 110% to 200% based on the degree of alignment (OI), and more specifically, may have a ratio of 115% to 180%, 120% to 160%, or 125% to 150%. flat ) is adjusted to satisfy the above range, so that the ab-axis crystal planes of the carbon-based negative active material contained in the flat portion are not aligned or the degree of alignment (OI flat ) is the alignment degree (OI) of the carbon-based negative electrode active material contained in the sliding part. sliding In comparison with the case where the ratio is more than 200% based on the total weight of the negative electrode active layer, the average lithium ion mobility of the entire negative electrode active layer is improved, so that the electrical resistance of the negative electrode is reduced and the energy density is further increased. In addition, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the sliding portion is reduced. sliding When the ratio is less than 100%, the electrical resistance of the negative electrode active layer in contact with the uncoated portion where the negative electrode tab is provided increases relatively, and deterioration is accelerated, so this can be prevented.

[0095] Furthermore, the sliding portion was analyzed by X-ray diffraction (XRD) spectroscopy to determine the intensity ratio of the peak representing the (0,0,4) crystal plane to the peak representing the (0,0,2) crystal plane (I 004 / I 002 Specifically, the strength ratio (I 004 / I 002The present invention relates to a method for determining the intensity ratio (I ) of the peak representing the (0,0,4) crystal plane and the peak representing the (0,0,2) crystal plane among the peaks detected during X-ray diffraction (XRD) spectroscopic analysis. 004 / I 002 ) within the above range, there are advantages in that an increase in direct current internal resistance can be suppressed, high rate characteristics are improved, and cycle life characteristics are improved.

[0096] Meanwhile, the negative electrode active layer according to the present invention may further selectively contain a conductive material, a binder, other additives, and the like, in addition to the negative electrode active material, as necessary.

[0097] The conductive material may include, but is not limited to, one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like.

[0098] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductive material.

[0099] At this time, the content of the conductive material may be 0.1 parts by weight to 10 parts by weight, specifically 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, or 0.5 parts by weight to 2 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the conductive material within the above range, the present invention can prevent the negative electrode resistance from increasing due to a low content of conductive material, resulting in a decrease in charge capacity. In addition, it can prevent problems such as a decrease in the content of the negative electrode active material due to an excessive amount of conductive material, resulting in a decrease in charge capacity, or a decrease in rapid charge characteristics due to an increase in the loading amount of the negative electrode active layer.

[0100] In addition, the binder is a component that aids in bonding between the active material and the conductive material and the current collector, and may be suitably used within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, and fluororubber.

[0101] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.

[0102] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 μm to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.

[0103] The negative electrode for a lithium secondary battery according to the present invention has the above-described configuration, and is therefore excellent in the effect of suppressing lithium deposition at the end of the negative electrode active layer during charging and discharging of the secondary battery. Therefore, a lithium secondary battery including the negative electrode has the advantage of being highly safe and capable of being charged and discharged for long periods of time under high-rate conditions.

[0104] <Lithium secondary battery> In one embodiment, the present invention further comprises: an electrode assembly including a positive electrode, the negative electrode according to the present invention as described above, and a separator disposed between the positive electrode and the negative electrode; and A lithium secondary battery including the electrolyte composition is provided.

[0105] The lithium secondary battery according to the present invention includes an electrode assembly in which a plurality of positive electrodes and a plurality of negative electrodes are alternately arranged with a separator disposed therebetween, and an electrolyte composition in the form of a lithium salt and an electrolyte additive dissolved in a non-aqueous organic solvent. The lithium secondary battery includes the negative electrode of the present invention in which the carbon-based negative electrode active material contained in the sliding portion of the negative electrode active layer is aligned (or oriented) vertically and / or nearly vertically based on the surface of the negative electrode current collector. As a result, the lithium secondary battery has the advantage of being highly safe since lithium deposition is prevented on the surface of the negative electrode active layer, especially on the edge, during charging and discharging of the battery, especially during charging and discharging under high rate conditions.

[0106] At this time, the negative electrode has the same structure as that described above, and therefore a detailed description thereof will be omitted.

[0107] In addition, the positive electrode includes a positive electrode active layer prepared by applying a positive electrode slurry containing a positive electrode active material onto a positive electrode current collector, drying and pressing the positive electrode active layer, and the positive electrode active layer may further include a conductive material, a binder, other additives, and the like, as necessary.

[0108] The positive electrode active material is a material capable of electrochemically reacting on a positive electrode current collector, and may include at least one of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 capable of reversibly intercalating and deintercalating lithium ions.

[0109] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2

[0110] [Chemical formula 2] LiM 2 p Mn q P r O4

[0111] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more of the elements W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつy+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is 0.05≦p≦1.0, q is 1-p or 2-p; r is 0 or 1.

[0112] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 above are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, have the advantage of being capable of stably supplying high capacity and / or high voltage electricity.

[0113] In this case, the lithium metal oxide represented by the above chemical formula 1 is LiNi0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., and the lithium metal oxide represented by the above chemical formula 2 is LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O 4、 LiNi 0.3 Mn 1.7 O 4、 LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiFe 0.5 Mn 0.5 PO4, etc., which may be used alone or in combination.

[0114] The positive electrode active material may be included in an amount of 85 parts by weight or more, specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the weight of the positive electrode active layer.

[0115] The positive electrode active layer may further include a conductive material, a binder, and other additives in addition to the positive electrode active material.

[0116] In this case, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include one or more of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.

[0117] The conductive material may be included in an amount of 0.1 to 5 parts by weight based on the weight of each positive electrode active layer, specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.

[0118] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.

[0119] The binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, based on the weight of each positive electrode active layer.

[0120] The total thickness of the positive electrode active layer is not particularly limited, but may be specifically 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.

[0121] In addition, the positive electrode may use a positive electrode current collector having high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, the average thickness of the current collector may be suitably applied to be 3 μm to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.

[0122] Meanwhile, the separator interposed between the positive and negative electrodes of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is one commonly used in the art, specifically, one containing at least one polymer selected from polypropylene, polyethylene, and polyethylene-propylene copolymers having chemical resistance and hydrophobicity may be used. The separator may have a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymer, and may have a composite separator formed by coating organic or inorganic particles on the porous polymer substrate with an organic binder. The separator may have an average pore diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.

[0123] Meanwhile, the lithium secondary battery according to the present invention is not particularly limited, but may be a secondary battery having a form including a stack type, a zigzag type, or a zigzag-stack type electrode assembly. As one example, the lithium secondary battery according to the present invention may be a pouch type secondary battery or a prismatic type secondary battery.

[0124] The negative electrode applied to the lithium secondary battery according to the present invention has an alignment degree (OI) of the carbon-based active material contained in the sliding portion of the negative electrode active layer. sliding ), it is possible to effectively suppress lithium deposition on the surface of the negative electrode active layer, specifically at the end, during charging and discharging of the secondary battery, even if the N / P ratio of the positive and negative electrodes stacked in the electrode assembly is less than 1. Therefore, the lithium secondary battery has the advantages of being highly safe and capable of being charged and discharged for long periods of time under high rate conditions.

[0125] The present invention will now be described in more detail with reference to examples and experimental examples.

[0126] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0127] <Examples 1 to 7. Production of negative electrodes for lithium secondary batteries> Natural graphite was prepared as the negative electrode active material, carbon black was prepared as the conductive material, and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were prepared as binders. 95 parts by weight of natural graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC), and 2.5 parts by weight of styrene butadiene rubber (SBR) were mixed with water to a solid content of 50% to 55% to form a negative electrode slurry, which was then applied at 100 mg / cm on a copper thin plate (thickness: 10 μm). 2 ~120mg / cm 2 The casting was done so that it would be like this.

[0128] Then, a magnetic field was applied to the entire surface of the slurry using magnets placed above and below the applied negative electrode slurry to induce the orientation of the natural graphite. The magnetic field was applied at an intensity of 1.0T to 1.2T for the time shown in Table 1 below. The magnet used to apply the magnetic field was a permanent magnet with a length ratio of 110% to 120% based on the width direction of the negative electrode slurry.

[0129] Thereafter, the copper sheet coated with the negative electrode slurry in which the orientation of the carbon-based negative electrode active material contained in the sliding part was induced was dried in a vacuum oven at 130°C, and then rolled to a density of 1.63±0.2g / cc to manufacture a negative electrode.

[0130] i) the sphericity of the carbon-based negative active material used in the manufactured negative electrode, and ii) the alignment degree (S 60 / 0 and O.I. sliding Specifically, i) the sphericity of the carbon-based negative active material was calculated by using an image obtained by a scanning electron microscope (SEM) to calculate the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the negative active material particles. In addition, ii) the degree of alignment (S 60 / 0 and O.I. sliding ) was measured by performing near-edge X-ray absorption fine structure (NEXAFS) spectroscopy and X-ray diffraction (XRD) spectroscopy on three arbitrary points on the flat and sliding parts of the negative electrode active layer. The measurement conditions for the near-edge X-ray fluorescence spectrometer (NEXAFS) and X-ray diffraction (XRD) are as follows.

[0131] (1) Near-edge X-ray fine structure (NEXAFS) spectroscopy -Accelerating voltage slit = 1 degree, receiving slit = 0.1 mm, scattering slit = 1 degree: 1.0 GeV ~ 1.5 GeV -Storage current: 80mA~350mA -Angle of incidence: 60° or 0°

[0132] (2)X-ray diffraction (XRD) spectroscopy - Target: Cu (Kα-ray) graphite monochromator -Slit: Divergence

[0133] Then, the degree of alignment (S 60 / 0 and O.I. sliding) were calculated and their average values ​​were calculated. The results are shown in Table 1 below.

[0134]

number

[0135]

number

[0136]

number

[0137] In formulas 1 to 3, S 60 / 0 is the peak intensity ratio when the X-ray incident angle is 0° (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ), I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

[0138] [Formula 4] OI=I 004 / I 110

[0139] In Equation 4, I 004represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy, I 110 represents the area of ​​the peak representing the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopy.

[0140] [Table 1]

[0141] <Comparative Examples 1 to 3. Production of negative electrodes for lithium secondary batteries> A negative electrode for a lithium secondary battery was manufactured by carrying out the same method as in Example 1, except that a) no magnetic field was applied to the surface of the negative electrode slurry coated on the copper sheet, or b) a magnetic field was applied only to the edge of the negative electrode slurry corresponding to the sliding portion of the negative electrode active layer.

[0142] In this case, when a magnetic field is applied only to the edge of the negative electrode slurry, the length ratio of the magnet to which the magnetic field is applied is adjusted to 100% or 110 to 120% based on the edge of the negative electrode slurry, i.e., the width direction of the sliding part.

[0143] In addition, i) the sphericity of the carbon-based anode active material used in each anode was measured, and ii) the degree of alignment (S) of natural graphite (i.e., the carbon-based anode active material) was measured by measuring near-edge X-ray absorption fine structure (NEXAFS) spectroscopy and X-ray diffraction (XRD) spectroscopy at each position in the anode active layer. 60 / 0 and O.I. sliding ), and iii) the ratio of the peak intensity representing the (0,0,4) plane to the peak intensity representing the (0,0,2) plane calculated from X-ray diffraction (XRD) (I 004 / I 002 ) are shown in Table 2 below.

[0144] [Table 2]

[0145] <Examples 8 to 14 and Comparative Examples 4 to 6. Production of Lithium Secondary Batteries> The positive electrode active material is LiNi with a particle size of 5 μm. 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive material and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.

[0146] A separator made of polypropylene having a thickness of 18 μm was interposed between the obtained positive electrode and the negative electrode prepared in each of the examples and comparative examples, and the resulting positive electrode was inserted into a case, and then an electrolyte composition was injected to assemble a lithium secondary battery.

[0147] The type of negative electrode applied to each lithium secondary battery is shown in Table 3 below.

[0148] [Table 3]

[0149] <Experimental Example 1> In order to evaluate the safety of the lithium secondary battery according to the present invention during high-rate charging and discharging, the following experiments were carried out on the lithium secondary batteries manufactured in the examples and comparative examples.

[0150] B) High-rate characteristics evaluation of secondary batteries First, each of the manufactured lithium secondary batteries was initially charged. Specifically, the lithium secondary batteries were initially charged at a temperature of 25° C. with a charging current of 0.3 C to a charge cut-off voltage of 4.2 V to 4.25 V, and the current density at the cut-off voltage was continued until it reached 0.02 C, thereby activating the batteries.

[0151] Each activated lithium secondary battery was fully charged at room temperature (22°C) at 0.1C-rate. The fully charged lithium secondary battery was then discharged at 0.1C-rate to measure the initial discharge capacity. Then, each lithium secondary battery was fully charged again at 0.1C-rate and discharged at 1.0C, 2.0C, 5.0C, and 9.0C-rates to measure the relative discharge capacity ratio based on the initial discharge capacity for each discharge rate. The measured discharge capacity ratios are shown in Table 4.

[0152] B) Safety evaluation of secondary batteries First, each of the manufactured lithium secondary batteries was initially charged. Specifically, the lithium secondary batteries were initially charged at a temperature of 25° C. with a charging current of 0.3 C to a charge cut-off voltage of 4.2 V to 4.25 V, and the current density at the cut-off voltage was continued until it reached 0.02 C, thereby activating the batteries.

[0153] Thereafter, each activated lithium secondary battery was charged at a temperature of 25°C with a charge current of 2.0C to a charge cut-off voltage of 4.2V to 4.25V, and discharged in a constant current mode until the current density at the cut-off voltage reached 0.02C. This charge / discharge cycle was counted as one cycle, and a total of 100 cycles were performed. Each lithium secondary battery that had undergone 100 cycles of charge / discharge was disassembled to confirm lithium deposition on the negative electrode surface. The results are shown in Table 4.

[0154] [Table 4]

[0155] As shown in Table 4, in the negative electrode for a lithium secondary battery according to the present invention, the carbon-based negative electrode active material contained in the sliding portion of the negative electrode active layer is aligned nearly perpendicular to the surface of the negative electrode current collector, thereby suppressing lithium deposition on the negative electrode surface and showing a high capacity retention rate during high-rate charge and discharge.

[0156] These results show that the negative electrode for a lithium secondary battery according to the present invention has an excellent effect of suppressing lithium deposition at the end of the negative electrode active layer during charging and discharging of the secondary battery, and therefore a lithium secondary battery containing it has high safety and is capable of long-term charging and discharging under high-rate conditions.

[0157] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.

[0158] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims.

Claims

1. a negative electrode current collector; and a negative electrode active layer provided on at least one surface of the negative electrode current collector and including a carbon-based negative electrode active material; The negative electrode active layer is divided into a flat portion having a constant thickness based on a cross-sectional structure, and a sliding portion disposed at an end of the flat portion and having a thickness gradient, The sliding portion has a value according to the following formula 1 of 1.0 or less when analyzed by near-edge X-ray absorption fine structure (NEXAFS). [0010] [0025] [0030] In Formulas 1 to 3, S 60/0 is the peak intensity ratio when the X-ray incident angle is 0° (I B/A ) at an X-ray incidence angle of 60° (I60 B/A ) I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

2. 2. The negative electrode of claim 1, wherein the degree of alignment (O.I) of the carbon-based negative electrode active material in the sliding portion is smaller than the degree of alignment of the carbon-based negative electrode active material in the flat portion: [Formula 4] O.I=I 004 / I 110 In formula 4, I 004 represents the area of ​​the peak representing the (0,0,4) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer.

3. 3. The negative electrode for a lithium secondary battery according to claim 2, wherein an alignment degree (O.I) of the carbon-based negative electrode active material contained in the flat portion is 110% to 200% based on an alignment degree of the carbon-based negative electrode active material contained in the sliding portion.

4. 3. The negative electrode for a lithium secondary battery according to claim 2, wherein the degree of alignment (O.I) of the carbon-based negative electrode active material contained in the sliding portion is 0.1 to 0.

6.

5. The sliding portion is a ratio (I) of the intensity of the peak representing the (0,0,4) crystal plane to the intensity of the peak representing the (0,0,2) crystal plane in X-ray diffraction (XRD) spectroscopy. 004 / I 002 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the ratio of the ionic strength of the negative electrode to the total ionic strength of the lithium secondary battery is 0.04 or more.

6. The negative electrode current collector is divided into a coated portion where the negative electrode active layer is disposed and a non-coated portion where the negative electrode active layer is not disposed, The negative electrode for a lithium secondary battery according to claim 1 , wherein the sliding portion contacts an uncoated portion on which a negative electrode tab is provided, among the uncoated portions.

7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the sliding portion has a width of 1 mm to 30 mm based on a cross-sectional structure of the negative electrode active layer.

8. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the carbon-based negative electrode active material comprises at least one of natural graphite and artificial graphite.

9. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the carbon-based negative electrode active material has a sphericity of 0.75 or more.

10. A lithium secondary battery comprising an electrode assembly including a positive electrode, the negative electrode according to claim 1 , and a separator disposed between the positive electrode and the negative electrode.

11. 11. The lithium secondary battery according to claim 10, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector and containing one or more positive electrode active materials selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2: [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O 2 [Chemical formula 2] LiM 2 p Mn 1-p O 4 In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are each in the range of 1.0≦x≦1.30, 0.5≦y<1, 0<z≦0.3, 0<w≦0.3, 0≦v≦0.1, and y+z+w+v=1; M 2 is Ni, Co or Fe, p is in the range of 0.05≦p≦1.

0.

12. The positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.2 O 2 , LiNi 0.9 Co 0.05 Mn 0.05 O 2 , LiNi 0.6 Co 0.2 Mn 0.1 A 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.15 A 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 A 0.1 O 2 , LiNi 0.7 Mn 1.3 O 4 , LiNi 0.5 Mn 1.5 O 4 , LiNi 0.3 Mn 1.7 O 4 , LiFePO 4 , LiFe 0.8 Mn 0.2 P.O. 4 , and LiFe 0.5 Mn 0.5 P.O. 4 The lithium secondary battery according to claim 11, comprising one or more of the following:

13. The lithium secondary battery according to claim 10, wherein the electrode assembly is a stacked type electrode assembly, a zigzag type electrode assembly, or a zigzag-stack type electrode assembly.

Citation Information

Patent Citations

  • Lithium ion secondary battery and manufacturing method therefor

    JP2013069579A

  • Nonaqueous electrolyte secondary battery

    JP2014086258A

  • Electrode Assembly Having Insulating Material Added on Outermost Surface and Secondary Battery Comprising the Same

    KR1020150028457A

  • Insulating Composition for Electrode of Secondary Battery and Electrode Comprising Electrode Tab Coated by the Same

    KR1020160125720A